Impact of low FODMAP sourdough bread on gut microbiota using an in vitro colonic fermentation model - Koc, Fatma; Arendt, Elke; Coffey, Aidan; Ross, R. Paul; Stanton, Catherine (Frontiers in Microbiology, 2024)
This study explores the development of whole-grain sourdough bread with reduced FODMAP (fermentable oligosaccharides, disaccharides, monosaccharides, and polyols) content to offer dietary solutions for individuals with irritable bowel syndrome (IBS). Three sourdough breads were prepared using different lactic acid bacteria (LAB) strains including Lactiplantibacillus plantarum FST1.7 (SD-FST1.7), Lacticaseibacillus paracasei R3 (SD-R3), and Pediococcus pentosaceus RYE106 (SD-RYE106). A control sourdough bread was prepared using baker’s yeast (SD-control). In vitro digestion and in vitro colonic fermentation were employed on bread samples with cellulose (negative control) and inulin (positive control), followed by 16S rRNA sequencing and short-chain fatty acid (SCFA) analysis to evaluate the impact on gut microbiota and SCFA levels. Alpha and beta diversity did not reveal any significant differences within the groups following in vitro colonic fermentation (FDR > 0.05). Taxonomic analysis displayed Firmicutes as the predominant phylum across all fecal samples at the end of colonic fermentation. Actinobacteriota was significantly lower in cellulose fermented fecal samples compared to samples fermented with SD-Control (ANCOMBC, FDR = 0.02) and inulin (ANCOMBC, FDR = 0.0001). Fecal samples fermented with inulin had significantly higher Bacteroidota levels compared to those fermented with cellulose (ANCOMBC, FDR =0.002). Acetate levels were higher in fecal samples fermented with SD-FST1.7 compared to those fermented with SD-R3 and SD-RYE106 (p = 0.03 for both). Positive correlations between butyrate and Lachnospira, Agathobacter, and Bifidobacterium were observed, demonstrating the potential of sourdough fermentation to influence gut health and support IBS management.